An Analysis of the Implementation of the Merdeka Curriculum in the Instruction of Integrated Natural and Social Sciences (IPAS) in Grade III at SDN 2 Lemahabang - Sanjaya, Chris; Fikriyah, Fikriyah (UM Purwokerto Press, 2025)
The issuance of the Regulation of the Minister of Education, Culture, Research, and Technology Number 12 of 2024 officially establishes the Merdeka Curriculum as the national curriculum, effective from the 2024/2025 academic year. A notable innovation of this curriculum is the integration of Natural Sciences (IPA) and Social Sciences (IPS) into a single subject called Integrated Natural and Social Sciences (IPAS), distinguishing it from previous curricular frameworks. Despite this advancement, the implementation of the Merdeka Curriculum, particularly in the context of IPAS instruction, has not yet fully achieved its intended objectives. This study aims to examine the implementation process, challenges encountered, and educational impacts of the Merdeka Curriculum in IPAS learning, grounded in its core principles. Utilizing a qualitative descriptive methodology, the research was conducted with Grade III teachers and students at SDN 2 Lemahabang. Data collection methods included observation, interviews, and document analysis, with data processed through reduction, display, and conclusion drawing techniques. Triangulation of sources and methods was employed to ensure data validity. Findings reveal that the implementation of IPAS within the Merdeka Curriculum framework is still partially misaligned with its foundational principles. Primary challenges involve time limitations during instruction and assessment phases, compounded by large class sizes. Nevertheless, the adoption of this curriculum has produced positive outcomes for both educators and learners.